2015
DOI: 10.1016/j.jebo.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance and single-sex schooling: Evidence from a natural experiment in Switzerland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 67 publications
1
55
1
1
Order By: Relevance
“…They also can show improvement when placed alongside peers with similar ability levels (Duflo et al 2011). There is also literature that finds positive effects of girls' presence in the classroom on student performance (Eisenkopf et al 2014;Hoxby 2000;Hu 2015;Oosterbeek and Van Ewijk 2013). Much of the literature focuses on peer effects between roommates at universities.…”
Section: Previous Literaturementioning
confidence: 99%
“…They also can show improvement when placed alongside peers with similar ability levels (Duflo et al 2011). There is also literature that finds positive effects of girls' presence in the classroom on student performance (Eisenkopf et al 2014;Hoxby 2000;Hu 2015;Oosterbeek and Van Ewijk 2013). Much of the literature focuses on peer effects between roommates at universities.…”
Section: Previous Literaturementioning
confidence: 99%
“…Other research indicates that female students benefit more from single-gender schooling compared to males (Alon and Gelbgiser 2011;Else-Quest and Peterca 2015;Lee and Bryk 1986;Mullholland et al 2004), with such environments suggested to lessen the impact of gender stereotypes on females' interest and performance in STEM-related subjects (Inzlicht and BenZeev 2003;Shapka and Keating 2003). For example, females report higher competence beliefs and tend to achieve higher grades in mathematics and science when they are taught in single-gender relative to co-educational schools (Eisenkopf et al 2015;Hoffman 2002).…”
mentioning
confidence: 99%
“…1 Direct evidence on single-sex education also largely confirms the benefits of homogeneous gender peer settings (Eisenkopf et al 2015;Jackson 2012;Lee et al 2014). Moreover, several studies have found that the gender composition of siblings also affects educational outcomes, but the evidence on gender peer effects of siblings is more mixed (Anelli and Peri 2015;Brunello and De Paola 2013;Butcher and Case 1994;Hauser and Kuo 1998;Parish and Willis 1993).…”
Section: Introductionmentioning
confidence: 95%